Direct oxidation of H-2 to H2O2 over different supported PdO catalysts in aqueous acidic medium: Influence of the reduction, calcination temperature and support of the catalyst on its net H2O2 formation activity - Choudhary, Vasant R.; Jana, Prabhas (Catalysis Communications, 2008)
Effects of the catalyst reduction (by hydrazine), calcination temperature (400-800 degrees C) and support (viz. Al2O3, SiO2, CeO2, ZrO2, HP or HM) on the performance of supported PdO (2.5 wt%) catalyst in the H-2-to-H2O2 oxidation (with H-2:O-2 = 1: 1) in an aqueous acidic (0.1 M H3PO4) medium under ambient conditions have been investigated. All the supported PdO catalysts showed lower H2 conversion activity, but higher H2O2 selectivity, as compared to their reduced counter parts. The catalyst performance for the net H2O2 formation is strongly influenced by both the support and calcination temperature of the supported PdO catalysts. The catalysts calcined at 400 degrees C showed better performance. Among the catalysts, PdO/Al2O3 catalyst (calcined at 400 degrees C) showed the best performance (17.0% H2O2 yield) in the H-2-to-H2O2 oxidation. The influence of the calcination temperature of PdO/Al2O3 catalyst on its H2O2 decomposition and hydrogenation activities has also been investigated. Both the H2O2 decomposition and hydrogenation activities increased with increasing the calcination temperature. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Hydrogen peroxide; oxidation of H-2 to H2O2; supported PdO catalysts

Direct oxidation of H-2 to H2O2 over PdO/Al2O3 catalysts in aqueous acidic medium: influence on H2O2 formation of Pd loading, calcination temperature and reduction of catalyst and presence of halide anions - Choudhary, Vasant R.; Jana, Prabhas (Catalysis Communications, 2008)
Effects of the Pd loading (0.2-10 wt%), calcination temperature (400-900 degrees C) and reduction of PdO/Al2O3 on its performance in the H-2-to-H2O2 oxidation (with H-2/O-2 = 1:1) in an aqueous 0.1 M H3PO4 medium, in the absence and presence of different halide anions, under ambient conditions have been investigated. The effect of calcination temperature on the H2O2 formation varied depending upon the Pd loading. The influence of the different halide anions was found to depend strongly on the nature of halide anion (F-, Cl-, Br- or I-) and the oxidation state of Pd and its loading in the catalyst. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: halide catalyst promoters; Hydrogen peroxide; oxidation of H-2 to H2O2; Pd/Al2O3; PdO/Al2O3